(untitled) (Italian Journal of Public Health, 2011)
Background: Risk assessment in relation to firearms and cognitive impairments is complex, and no guidelines exist regarding the appropriate management of people with dementia who may own or have access to a firearm. In Italy, approximately 4.8 million people either own a firearm or use one for recreational, sporting or professional reasons. Recent studies report that firearms were used in 35.7% of suicides committed by people over 65 years old and that 5% of all suicides were committed by over 65-year-olds using firearms. As for the figures related to homicides committed with firearms by people over 65, these represented 31.8% of all homicides committed with firearms. Results: The aim of the present study was to conduct a critical review of the procedures currently used in relation to the use of firearms by elderly people. We conducted a review of the international scientific literature published over the last 20 years on the phenomenon of firearms abuse by elderly people and its prevention, drawn from the Medline and PsychINFO online databases. We considered all studies published in journals and books from 1990 to 2010 using the following keywords: violence, firearms, suicide, homicide, dementia and cognitive impairments, and searching for quantitative studies, case reports and literature reviews. Conclusions: Family physicians and specialists (geriatricians, neuropsychiatrists, clinical psychologists) can act as an indispensable observatory of the related risks in people who own firearms, but their role should be supported by suitable training on the procedures used to assess and report on any such risks.